Meeting phenomena of red blood cells in rolls of coins and irregular agglomerates. Sedimentation rate of red blood cells. Blood groups. techniques - Ciotola, Enrique (1927)
(Continued). Current status of research relating to the number of  soagglutinins and isoaglutinógenos present in human blood.